Three-level Converter in Offshore Wind Energy Systems: New Strategy for Unbalancing in Capacitors Voltage - Seixas, Mafalda (2015)
This paper is on an offshore wind energy conversion system equipped with full-power three-level converter and permanent magnet synchronous generator. Multi-level converters, namely three-level converters, are limited by unbalance voltage in the direct current link capacitors. A new control strategy for the selection of the output voltage vectors is proposed in order to improve balance of voltage in the capacitors.